Formulation of fish waste meal for human nutrition - Rodrigues de Souza, Maria Luiza; Yoshida, Grazyella Massako [UNESP]; Vasconcelos Campelo, Daniel Abreu; Moura, Lorena Batista de; Xavier, Tadeu Orlandi; Reis Goes, Elenice Souza dos (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2017)
This study aimed to elaborate and characterize meals containing waste from processing of tilapia, tuna, salmon and sardine for human consumption. Carcasses of tilapia and salmon, tuna torsos without fins and sardine tails were cooked, pressed, milled and dehydrated, resulting in waste meal. Greater protein (83.28%) and lower mineral matter (5.31%) were observed in tuna meal. Salmon meal presented greater content of lipids (18.81%) and sardine meal, lower content (3.98%). Tilapia meal presented greater mineral matter (37.66%), calcium (9.37%) and phosphorus (6.08%). Higher content of iron was observed in sardine and tuna meals. Higher amounts of fatty acids from n-3 series were found in salmon (53.71 g kg(-1)), sardine (47.46 g kg(-1)) and tuna (36.98 g kg(-1)). Concerning amino acids, glutamic acid showed greater proportion in all meals, followed by lysine, leucine, glycine and aspartic acid. All meals presented high biological and nutritional values and are regarded as important sources of calcium, phosphorus and iron.
Keywords: waste reuse; Nile tilapia; salmon; tuna; sardine